SEBARAN MIKROORGANISME TANAH PADA BEBERAPA PENGGUNAAN LAHAN PERTANIAN DI KALIMANTAN BARAT - Murni, Sri Dewi; Fadilla, Ulfia (Fakultas Pertanian, Universitas Janabadra, 2023)
The utilisation of suboptimal land for agricultural activities affects the amount of microbial distribution. This research aims to see the distribution of microbes on several land uses in West Kalimantan. Soil sampling was conducted on 3 land uses, agriculture, plantation, and secondary forest. This research was conducted in March - June 2023. Soil samples were taken at a depth of 0-20 cm with 3 replicates per land use. The parameters observed included the total population of bacteria and fungi, and respiration. The results showed that the total population in oil palm plantations had a respiration value and the total bacterial population had a value of 3.9 mgCO2/g/m2/day and 52.5 x 10-3 cfu/g soil, respectively, higher than the secondary forest and agricultural land uses. The total population value of fungi on agricultural land is superior to oil palm plantations and secondary forests at 8.75 x 10 - 5 cfu/g soil. Keyword: land use; microorganism; respiration. INTISARIPemanfaatan lahan suboptimal untuk kegiatan pertanian mempengaruhi jumlah sebaran mikroorganisme. Penelitan ini bertujuan untuk melihat sebaran mikroorganisme pada beberapa penggunaan lahan di Kalimantan Barat. Pengambilan sampel tanah dilakukan pada 3 penggunaan lahan, pertanian, perkebunan, dan hutan sekunder. Penelitian ini dilakukan pada bulan maret – juni 2023. Sampel tanah diambil pada kedalaman 0 – 20 cm dengan 3 ulangan per penggunaan lahan. Parameter yang diamati meliputi total populasi bakteri dan jamur, dan respirasi. Hasil penelitian menunjukkan total populasi pada perkebunan sawit memiliki nilai respirasi dan jumlah total populasi bakteri masing-masing memiliki nilai 3,9 mg CO2/g/m2/hari dan 52,5 x 10-3 cfu/g tanah, lebih tinggi dibandingkan dengan penggunaan lahan hutan sekunder dan pertanian. Nilai total populasi jamur pada lahan pertanian lebih unggul dibandingkan lahan perkebunan sawit dan hutan sekunder sebesar 8,75 x 10 - 5 cfu/g tanah. Kata kunci: mikroorganisme; penggunaan lahan; respirasi